2006
DOI: 10.1111/j.1530-0277.2006.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

DOVER and QUVER—New Marker Combinations to Detect and Monitor At‐risk Drinking

Abstract: Our study is to date the largest practice-based trial that examines the value of the markers CDT and gamma-GT and their combinations for the screening of at-risk drinking in general practice under routine conditions. Our ROC analysis clearly demonstrated that the combination of the markers gamma-GT and %CDT under routine conditions with a behaviorally oriented reference standard leads to an improvement of diagnostic performance, more so than the use of single markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…However, in a broad sense, the utility of these biomarkers as diagnostic tools is greatly hampered due to variable results in different populations and low sensitivity and specificity. For example, clinical studies of CDT have found a range of sensitivities (77–100%) and specificities (10–85%) (Berner et al, 2006;Koch et al, 2004;Miller et al, 2006). These limitations may arise from several factors.…”
Section: Current Biomarkers Of Alcoholismmentioning
confidence: 99%
“…However, in a broad sense, the utility of these biomarkers as diagnostic tools is greatly hampered due to variable results in different populations and low sensitivity and specificity. For example, clinical studies of CDT have found a range of sensitivities (77–100%) and specificities (10–85%) (Berner et al, 2006;Koch et al, 2004;Miller et al, 2006). These limitations may arise from several factors.…”
Section: Current Biomarkers Of Alcoholismmentioning
confidence: 99%
“…Selin (9), for example, concluded that an AUDIT questionnaire (containing all 10 items) reliably discriminates between four differently defined alcohol-related problems (excessive consumption, alcohol-related social problems, alcoholinduced health problems, and alcohol dependence). Berner et al (10) confirmed good AUDIT validity through the application of objective biological markers (CDT and GGT). They concluded that a screening questionnaire in combination with laboratory tests improve diagnostics in comparison to the separate use of any of the methods.…”
Section: Discussionmentioning
confidence: 92%
“…For AUDIT-C, we considered a score of ≥5 (out of a possible 12 points) positive for a man and ≥2 positive for a woman (Bradley et al, 2003, 2007; Gordon et al, 2001). The cut-off for %CDT was 2.6% as recommended by the manufacturers (Axis Shield ASA, Oslo, Norway; Berner et al, 2006). We assumed all screen-positive patients completed a full clinical assessment (i.e., the gold standard) for unhealthy alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…Heavy daily consumption of alcohol for 2 weeks or more triggers a positive test. Studies have found that %CDT has high specificity (77 to 100%) but variable sensitivity (10 to 85%) (Berner et al, 2006; Koch et al, 2004; Miller and Anton, 2004). Performance estimates vary depending on whether the goal of screening is to detect very heavy drinking (>60 to 80 g of ethanol or more than 5 to 7 drinks per day) or the at-risk amounts defined above.…”
mentioning
confidence: 99%